Sovereign wealth funds : states buying the world - Loh, Lixia (Hawkhurst, Kent : Global Professional Publishing, 2010)
This book aims to clarify the nature, strategies and investment holdings of SWFs to enable policymakers, academics and potential investment targets to make reasoned judgements on the significance and activities of this fast-growing phenomenon. It focuses on their operations, investment activities and strategies, and the implications of SWFs in the global markets.
Includes bibliographical references (p. 205-212) and index.
oif 16/05/14
Loan
Keywords: Sovereign wealth funds; Sovereign wealth funds -- Case studies; Investments, Foreign; International economic relations